Uni-Morbid and Co-Occurring Marijuana and Tobacco Use: Examination of Concurrent Associations with Negative Mood States - Bonn-Miller, Marcel O. (2010)
The aim of the current investigation was to examine uni-morbid and co-occurring tobacco and marijuana use in relation to the negative emotional symptoms of anxiety and depression. Participants were 250 adult individuals (132 female; m(age) = 22.43, SD = 9.00), falling into one of four non-overlapping substance use categories: tobacco use only (n = 39), marijuana use only (n = 62), co-occurring tobacco and marijuana use (n = 82), and neither tobacco nor marijuana use (n = 67). Results revealed three key findings. First, tobacco-only using individuals reported significantly greater negative affectivity than any of the other groups. Second, tobacco-only users reported greater anxious arousal symptoms than either the marijuana or non-substance-using groups, but not the combined group. Third, tobacco-only users reported greater levels of depressive symptoms than either marijuana users or non-substance-users. These findings provide novel information about tobacco and marijuana use, and how these variables relate to the experience of general and specific types of negative emotional symptoms.